Influence research of settlement grid parameters on characteristics of compressor cascades - Кирчу, Федор Иванович (Eastern-European Journal of Enterprise Technologies, 2012)
We studied the dependence of the rotation angle of the flow and total pressure losses in the compressor grating parameters of the computational grid. The advantages and disadvantages of certain types of computational grids